Three new species of the genus Tartessus Stål (Hemiptera: Cicadellidae: Tartessinae) from Vietnam - Gnezdilov, Vladimir M. (Zootaxa, 2020)
Three new species of the genus Tartessus Stål,  1865 are described from Vietnam: T. kabakovi sp. n.—from Vinh Phuc Province; T. nigriventris sp. n.—from Gia Lai Province; T. iridescens sp. n.—from Ðồng Nai and Bà Rịa-ũng Tàu Provinces. These are first records of the subfamily Tartessinae from the country. T. malayus (Stål, 1859) is recorded and illustrated from Taiwan.